Meta‐analysis comparing denosumab and zoledronic acid for treatment of bone metastases in patients with advanced solid tumours. (19th July 2016) - Zheng, G.Z.; Chang, B.; Lin, F.X.; Xie, D.; Hu, Q.X.; Yu, G.Y.; Du, S.X.; Li, X.D.
Abstract : The purpose of this meta‐analysis was to evaluate the efficacy of denosumab, compared with zoledronic acid (ZA), in delaying skeletal‐related events (SREs) and enhancing overall survival in patients with advanced solid tumours and bone metastases. A systematic literature search of several electronic databases, including PubMed, Medline, Embase, the Cochrane Library, CKNI and Web of Science with Conference Proceedings, was performed. Only randomised controlled trials assessing denosumab in comparison with ZA, in patients with advanced solid tumours and metastatic‐stage disease, were included. The primary outcome was the time to first SRE. The risk of developing subsequent on‐study SREs and overall survival were also evaluated. Three randomised controlled trials with a total of 5, 544 patients with advanced solid tumours and bone metastases were included in the meta‐analysis. There were 2, 776 patients treated with denosumab and 2, 768 treated with ZA. The pooled analysis showed that denosumab was superior to ZA in delaying time to first on‐study SRE (odds ratio [OR]: 0.82; 95% CI: 0.75–0.89, p  < 0.0001) and multiple SREs (risk ratio: 0.81; 95% CI: 0.74–0.88, p  < 0.0001). However, no significant difference was found in overall survival improvement between denosumab and ZA (OR: 1.02; 95% CI: 0.91–1.15, p  = 0.71). This meta‐analysis indicates that denosumab is superior to ZA in delaying SREs for patients with bone metastases. No significant difference was observed between denosumab and ZA, regarding overall survival. We support denosumab as a potential novel treatment option for the management of bone metastases in advanced solid tumours.